2021
DOI: 10.51535/tell.855775
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of the COVID-19 Pandemic in the Development of Preschool Children and Protective Factors

Abstract: The coronavirus epidemic that erupted in Wuhan, China, in 2019, spread rapidly and affected the entire world. The fight against the epidemic has brought about many changes in people's lives and relationships, including preschool children, who are affected by the epidemic process. Preschool is a phase in which development is rapid and environmental factors have a high impact on development that encompasses many critical development phases. In this rapid development phase, the impact of the Covid-19 pandemic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
0
2
0
2
Order By: Relevance
“…Survey responses from parents of young children suggest that children's physical activity levels decreased and sedentary behaviors (e.g., watching television, using screen devices, and playing video games) increased during the early months of the pandemic, with parental anxiety potentially mediating these effects [62,63]. If these sedentary patterns continue after stay-at-home orders are relaxed, children without preexisting developmental disorders may be at risk for delayed development of gross motor skills that are formed from activities like running, jumping, and balancing [64]. A study also showed that higher screen time exposure during early childhood was associated with more autism spectrum disorder (ASD)-like behaviors due to the adverse impact of excessive screen time on social learning, brain processing, and the potential to promote visual brain hyperconnectivity [65 ▪ ].…”
Section: Developmental and Behavioralmentioning
confidence: 99%
“…Survey responses from parents of young children suggest that children's physical activity levels decreased and sedentary behaviors (e.g., watching television, using screen devices, and playing video games) increased during the early months of the pandemic, with parental anxiety potentially mediating these effects [62,63]. If these sedentary patterns continue after stay-at-home orders are relaxed, children without preexisting developmental disorders may be at risk for delayed development of gross motor skills that are formed from activities like running, jumping, and balancing [64]. A study also showed that higher screen time exposure during early childhood was associated with more autism spectrum disorder (ASD)-like behaviors due to the adverse impact of excessive screen time on social learning, brain processing, and the potential to promote visual brain hyperconnectivity [65 ▪ ].…”
Section: Developmental and Behavioralmentioning
confidence: 99%
“…Poleg tega pa so poudarili vlogo vodstva in odgovornih institucij. V literaturi (Gayatri 2020;Saltalı 2021;Stoiljković 2020) še zasledimo, da je epidemija covida-19 vplivala na številna področja otrokovega razvoja -tako čustvenega, socialnega, motoričnega, miselnega, psihičnega, kot tudi na razvoj govora. Zato sta redno vključevanje otroka v vrtec in sodelovanje s starši ključnega pomena.…”
Section: Literaturaunclassified
“…Mask-wearing was a new and unusual health behavior for the majority of Americans, leading to speculation about how young children (under age 6) might comply (Esposito & Principi, 2020; Jin et al, 2020). Developmentally, young children could have a hard time keeping a mask on and wearing it correctly (Saltalı, 2021). Also, as young children are learning to speak, listen, and communicate, masks covering facial cues during a conversation could impede learning (Stajduhar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%